Prem Baby Triple P a new parenting intervention for parents of infants born very preterm: Acceptability and barriers - Ferrari, A.; Whittingham, K.; Boyd, Roslyn; Sanders, M.; Colditz, P. (2011)
Over 10% of preterm infants develop major disabilities, 50% develop behavioural problems and 40% need special education (Huddy et al., 2001; Webster, 2003). Prem Baby Triple P is a new variant of the Positive Parenting Program (Triple P) adapted specifically for parents of very preterm infants. The aim of this study is to assess the acceptability of Prem Baby Triple P to parents of infants born preterm and to test whether parental attributions and parental perception of infant health/developmental status are barriers to intervention acceptability. One hundred and twenty-three parents of preterm infants participated, 83 parents of very preterm infants and 40 parents of preterm infants. In addition, 32 parents of term infants participated as a comparison group. The acceptability of Prem Baby Triple P was moderately high and did not differ significantly across the three groups. Parental attributions were not found to be barriers to intervention acceptability and parental perceptions that their infant is less healthy/developmentally delayed facilitated Prem Baby Triple P acceptance in parents of infants born very preterm. This suggests that the planned Prem Baby Triple P content is acceptable to parents of infants born very preterm and sensitised to medical and developmental issues. These findings, as social validation data, will contribute towards the further development of Prem Baby Triple P and a future randomised controlled trial. © 2011.